The Sociotechnical Axis of Cohesion for the is Discipline: Its Historical Legacy and its Continued Relevance1 - Sarker, Suprateek; Chatterjee, Sutirtha; Xiao, Xiao; Elbanna, Amany (MIS Quarterly, 2019)
The sociotechnical perspective is often seen as one of the foundational viewpoints—or an “axis of cohesion”— for the Information Systems (IS) discipline, contributing to both its distinctiveness and its ability to coherently expand its boundaries. However, our review of papers in the two leading IS journals from 2000 to 2016 suggests that IS research has lost sight of the discipline’s sociotechnical character—a character that was widely acknowledged at the discipline’s inception. This is a problem because an axis of cohesion can be fundamental to a discipline’s long-term vitality. In order to address this issue, we offer ways to renew the sociotechnical perspective so that it can continue to serve as a distinctive and coherent foundation for the discipline. Our hope is that the renewed sociotechnical frame for the IS discipline discussed in the paper holds potential to contribute to the enduring strength of our diverse, distinctive, yet unified discipline. It also prompts members of the discipline to think more deeply about what it means to be an IS scholar.